An empirical study on the personal and social adjustmants of the UPV fresmen. - Balinas, Anna Brena A. (1981.)
no abstracts
Research Paper (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: UPV freshmen -- Personal adjustments; UPV freshmen -- Social adjustmants